Cuidadores familiares de idosos com síndromes demenciais: narrativas sobre o cuidado - Ribeiro, Corina Lopes [UNIFESP] (2018)
The increasing in life expectancy elevates the possibility of the population live and deal with chronic-degenerative diseases. Besides those diseases, some dementia syndromes have been causing a socio-economic impact, in family structure, society, healthcare system, performing as an important public healthcare problem. Such syndromes are the main reason in the incapability in aging, demanding the nurse from others, just as the assistance in instrumental everyday activities. The nurse is frequently offered by the family, which it tends to be a female family member, and grieves with the influence from personal experiences and sociocultural practice, besides the refocusing from the elderly with dementia by the family. This care is permeated by affection relationships through history life, conflicts, affection, interdictions, worths, obligations and shared hopes. For Heidegger, Daisen (Being there) is essentially regarded and there is the sense of helpfulness and sorrow, as essential and conflicting possibilities. The <anguish nurse= (Sorge) refers to each one?s struggle to survive and achieve a convenient position compared with others human beings. The <helpfulness nurse= (Fürgsorge) portrays, turns back to, being interested in humanity and in Earth. In the meantime the care as anguish moves mankind in the internal struggle for livelihood, the care along helpfulness shows mankind?s potentialities. This study objective was to comprehend the meaning of the family?s caretakers care toward elderly people with dementia syndromes. The qualitative method was drew on with interviews questionnaire schedule, restrict to five guiding questions to produce data and build of a life history narratives. The survey participants were six caretakers from elderly families attended by the Medical Specialties Ambulatory from Santos City. The data analyses was held through commentaries and interpretation, based in Heidegger and Daseinsanalyse?s suppositions stem from life history narratives. The caretakers related the anguish in the face of the lost of elderly possibilities with the disease advancement. They feel alone and overwhelmed in performing the care and it doesn?t matter the help type or quality, there is a difficulty in noticing people?s collaboration. On the other hand, family members are offloaded or disclaimed by having others activities such as work or offspring raise. It?s notable the conflict between the ideal care and the possible care, such as the constant obligation of being patient. The significances attached to care were obligations, debt and duty, satisfaction for the elderly well-being and as a consequence, its own well-being, prize and love. The life histories reveal previous relationship of affection and estrangement, that the care turned possible in a new sense, as acloseness between the caretaker and the elderly person and the reinforcement of feelings as love. The care has also exhibited as an opportunity of personal discovering and growth. The disease entails a restriction on the elderly person and the caretakers, by restricting the existence and the being with others. The survey results can subsidize the practice and intervention plans along with the family caretakers, as well as, instigate new necessary surveys to think about the sharing care, expanding and strengthening the formal and informal support. So that this method, the family caretakers will not feel so lonely and overwhelmed, thus they can also contemplate the potentiality in caring in being with the other, this often harsh journey of living with a family member with dementia syndrome.